Analysis of Goat Farming on Integrated Farming System in Banyumas - Hidayat, NN (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2007)
The objective of this research were : 1) to find out the income generated from goat farming and its contribution to farmer income in several farming combination, 2) to find out the economic efficiency in goat farming with paddy and fish production, 3) to determine factors affecting level of production and income in different farming system, partially and aggregately, and 4) to determine the best combination of farming which generated maximum income. Household farmer survey method was performed to conduct this research. Farming model chosen in this research was partial and average aggregate. Cobb-Douglas function were chosen to predict functional relationship. Result stated from this research were : 1) goat farming has a significant contribution in integrated farming system, 2) integrated farming (goat and paddy, goat and fish, and goat, fish and paddy) in Banyumas district was economically efficient. 3) partially, factor affecting production level in goat farming was number of goat owned (P<0.01), factor affecting paddy production were urea application and number of land owned (P<0.01), TSP application (P<0.05) and man power (P<0.10). Furthermore, factor affecting fish farming were feed, breed and number of land owned (P<0.01); 4) aggregately, factor affecting integrated farming I were urea application and number of land owned (P<0.01), feed and number of land owned (P<0.01), number of goat owned (P<0.10) integrated farming II, where as in integrated farming III were number of paddy land area and breed (P<0.01) also number of goat owned (P<0.10); 5) integrated farming III (goat, paddy and fish farming) gave the highest profit, which gave Rp 6.219.283,81 with relatively high efficiency. Therefore, goat farming could be an alternative solution to be developed in integrated farming and could be combined with other farming activities such as paddy and fish farming. (Animal Production 9(2): 105-110 (2007) Key Words : Goat, income, economic efficiency, survey, contribution, integrated farming